2015
DOI: 10.1021/acs.iecr.5b02617
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Mean Residence Time of Liquid Phase in the Gas–Liquid Cyclone

Abstract: Residence time is a key parameter for the cyclones with mass transfer or reaction process. A model for the cylinder-on-cone cyclone was presented to calculate the mean residence time of the liquid phase, based on a force balance on the wall film. This model was validated using an experiment, which measured the residence time of the liquid phase by the hold-up method. The results demonstrated that the predicted residence times are in good overall agreement with the measured values. Furthermore, the liquid resid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…In fact, the study of USLF is by no means limited to the GLCC separator. This kind of swirling liquid film is universal in any gas-liquid separators or pipes with tangential inlets (Ahmed et al, 2011); (Yang et al, 2015) or helical vanes (Kataoka et al, 2009); (Xiong et al, 2014); (Funahashi et al, 2018). Compared with the ordinary annular flow in a gas-liquid twophase pipe, the swirling liquid film has two distinct characteristics: 1) The movement of the liquid film includes not only an axial component but also a tangential component;…”
Section: Introductionmentioning
confidence: 99%
“…In fact, the study of USLF is by no means limited to the GLCC separator. This kind of swirling liquid film is universal in any gas-liquid separators or pipes with tangential inlets (Ahmed et al, 2011); (Yang et al, 2015) or helical vanes (Kataoka et al, 2009); (Xiong et al, 2014); (Funahashi et al, 2018). Compared with the ordinary annular flow in a gas-liquid twophase pipe, the swirling liquid film has two distinct characteristics: 1) The movement of the liquid film includes not only an axial component but also a tangential component;…”
Section: Introductionmentioning
confidence: 99%
“…4 The GLCC separators were developed by the Tulsa University Separation Technology Projects team in 1995, and since then, different studies have been developed around the relevant parameters of design and operation. 5,6 For instance, Yang et al 7 studied the residence time of the liquid phase in a cyclonic separator, obtaining that the liquid residence time decreases with the increasing of droplets loading, while the decrease is smaller when the inlet velocity increases. On the other hand, the liquid residence time increases with the cylinder diameter.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Assuming that all of the liquid was gathered at the wall of the cyclone to form the liquid film under the impact of the centrifugal force, he derived a theoretical liquid film residence time calculation model based on the force balance on the gas and liquid phase in the axial direction. To verify the accuracy of the Hoffmann model, Yang et al 22 performed a cold model experiment to investigate the average liquid film residence time in a gas-liquid cyclone using a holdup method. The experimental results showed that the liquid residence time obviously decreased with an increase in inlet liquid holdup and decreased less with an increase in inlet gas velocity.…”
Section: Introductionmentioning
confidence: 99%